Ecosystem Architecture Management in the Public Sector – From Problems to Solutions - Jarkko Nurmi; Ville Seppänen; Meri Katariina Valtonen (Complex Systems Informatics and Modeling Quarterly)
Based on our research concerning enterprise architecture (EA) in the Finnish public sector, we discuss how EA concept and tool need to be developed to support government business ecosystem and organization design. Our research context indicates, beyond a federal government or a state one, that even a single municipality, like a city concern, can be perceived as an ecosystem of its sectoral domains, subsidiaries and such. We outline a vision of an overall ontology-based, shared EA repository for the-whole-of-government current state descriptions and specify the central design principles and functional requirements for such a system, illustrating some potential use cases of it. Based on interview data from four smart city cases in Finland, we suggest a management model for the government ecosystem architecture target state design, specifically a design process for co-creating new services in the ecosystem. Further, we outline some principles for government ecosystem architecture management.